(untitled) (Research, Society and Development, 2021)
Silicon (Si) is the second most abundant element in the earth’s crust. This element is found in the form of oxides (SiO2), constituting the silicate minerals that form rocks and sediments such as sand, silt and clay. However, it is not considered essential for the full development of plants, due to acting only indirectly in the development of these, being therefore considered a beneficial element. Si can act by increasing the photosynthetic capacity, reducing the transpiratory rate, providing greater resistance to biotic and abiotic stresses. The presence of Si in tropical soils is low, due to the intense weathering process that occurs in these. Thus, in Brazil, many researchers are dedicated to the study of this element, aiming to identify the benefits provided and understand the conditions of occurrence. Thus, the present literature review aims to compile information about Si, and its role in plants, as a mitigation of biotic and abiotic stresses.